PERANCANGAN WEB OBJEK WISATA DIKABUPATEN TAPANULI UTARA - Arsy Tessalonika Silaban; Roni J. Simamora; Eva Julia G. Harianja (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2022)
Tapanuli Utara has many tourist objects, however, people don’t know much because of limited information about these attractions. Based on this, the author proposes this final project as a medium in an effort to increase further recognition of tourism objects in Tapanuli Utara. Information on tourist attractions can be accessed through a website that has been designed. The research method used is by making direct observations of the system that is running at the Office of the Tourism Office of Tapanuli Utara and conducting direct interviews with employees in the promotion information section and tourism resources. The results of this study are a web-based tourist attraction information system in North Tapanuli Utara which has a more attractive appearance and at the same time becomes another alternative for the community besides the official website owned by the relevant agency. This research produces an information system regarding tourism objects, accommodations, products, and events that are held in Tapanuli Utara. With the addition of images, descriptions, and locations.